STUDY THE GROWTH KINETICS OF PEDIOCOCCUS ACIDILACTICI WITH ESTIMATION OF KINETIC PARAMETERS AND APPLIED IN LARGE SCALE PEDIOCIN PRODUCTION - Mandal, Barnali (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: The aim of the study was to determine the growth kinetics of Pediococcus acidilactici using a mathematical model for large scale pediocin production. Methods: Growth kinetics of P. acidilactici has been studied for pediocin production in small scale batch fermenter (Erlenmeyer flask) using meat processing waste medium. The experiments have been conducted with varying the concentrations of glucose, protein, and lactic acid. A mathematical model has been developed to describe growth rate, products (pediocin and lactic acid) formation rate, and substrates (glucose and protein) utilization rate. Monod model for dual substrates (glucose and protein) has been used with considering lactic acid inhibition. Luedeking-Piret model has been introduced to describe the production of pediocin and lactic acid. Results: The values of kinetic parameters have been determined using experimental data and model equations. The model prediction has been compared satisfactorily with the experimental data for the validation of the model. Conclusions: The developed model was satisfactorily validated to scale up the production of pediocin. Keywords: Pediococcus acidilactici, Pediocin, Meat processing waste, Monod model, Luedeking-Piret model, Kinetic parameters.